Basalt fiber as a skeleton to enhance the multi-conditional tribological properties of epoxy coating. (May 2023) - Huang, Yu; Cai, Meng; He, Can; Si, Chengyi; Li, Le; Fan, Xiaoqiang; Zhu, Minhao
Abstract: Randomly distributed basalt fibers were used as the skeleton to enhance the tribological properties of epoxy coating, because the evenly-dispersed basalt fibers can offer the interior/exterior enhancement under drying, corrosion and UV aging. The composite coating with 2 wt% basalt fibers gives the best tribological properties, in which the wear rate after friction in brine is reduced by 76.03 %, with pure epoxy as comparison. The nailing effect from interlocking internal structures and strengthening mechanism from slightly convex bearing structure of basalt fiber on the coating were verified by dynamic mechanical analysis and scanning electron microscope. Herein, excellent construction and tribological behaviors of short-cut basalt fiber as filler provide a good protection strategy for epoxy resin application. Graphical Abstract: ga1 Highlights: A freely dispersed basalt skeleton was successfully constructed in epoxy coating. The epoxy coating with 2 wt% basalt fibers (BF-2#) performs well under dry, tribocorrosion and after-UV friction conditions. The wear rate of BF-2# decrease by 76.03 % under dry friction. The composite coating has excellent bearing capacity and deformation resistance.